2018
DOI: 10.1080/17435390.2018.1463407
|View full text |Cite
|
Sign up to set email alerts
|

Silicon dioxide nanoparticle exposure affects small intestine function in anin vitromodel

Abstract: The use of nanomaterials to enhance properties of food and improve delivery of orally administered drugs has become common, but the potential health effects of these ingested nanomaterials remain unknown. The goal of this study is to characterize the properties of silicon dioxide (SiO) nanoparticles (NP) that are commonly used in food and food packaging, and to investigate the effects of physiologically realistic doses of SiO NP on gastrointestinal (GI) health and function. In this work, an in vitro model comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 112 publications
2
36
1
Order By: Relevance
“…At cellular level, SiO 2 NMs destroyed the brush border by interacting with intestinal micro villi in coculture model of Caco2/HT29MTX, which inhibited the absorption of nutrients, such as iron, zinc, glucose, and lipid. [49] As important metal nanomaterials, pristine Ag NMs can also induce cytotoxicity and DNA damage through oxida tive stress in intestinal epithelial cells or coculture of epithe lial and immune cells; [50][51][52][53][54] even worse, these nanomaterials could disrupt the structure of intestinal villi at animal level. [48] In addition, some studies have shown that the intestinal micro environment, such as intestinal fluid and food matrix, is likely to alter NMs' effects on IECs.…”
Section: Nano-iec Interaction and Subsequent Biological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…At cellular level, SiO 2 NMs destroyed the brush border by interacting with intestinal micro villi in coculture model of Caco2/HT29MTX, which inhibited the absorption of nutrients, such as iron, zinc, glucose, and lipid. [49] As important metal nanomaterials, pristine Ag NMs can also induce cytotoxicity and DNA damage through oxida tive stress in intestinal epithelial cells or coculture of epithe lial and immune cells; [50][51][52][53][54] even worse, these nanomaterials could disrupt the structure of intestinal villi at animal level. [48] In addition, some studies have shown that the intestinal micro environment, such as intestinal fluid and food matrix, is likely to alter NMs' effects on IECs.…”
Section: Nano-iec Interaction and Subsequent Biological Effectsmentioning
confidence: 99%
“…[93] Copyright 2016, Elsevier Ltd. in vivo. [30,49,54,60,88] These nanomaterials can induce oxidative stress, nitrifying stress (NO), lipid peroxidation, organelles damage (mitochondria and lysosomes), and DNA damage, thus triggering inflammatory responses. [4,54] Along with the effects of NMs per se, a variety of compounds, including phe nolic compounds, quercetin, kaenol, free fatty acid (FFA), and reduced the toxicity of Ag and ZnO NMs on intestinal epithelial cells through maintaining the integrity of epithelial barrier and decreasing the level of oxidative stress, protected the epithelial cells from the damage of inflammatory response.…”
Section: Effects Of Nanomaterials On Intestinal Immunity and Their Pomentioning
confidence: 99%
“…HT29-MTX cells represent goblet cells and form a protective mucus layer on top of the Caco-2 cell layer (Lesuffleur et al, 1995). The Caco-2/HT29-MTX co-culture system has been used previously to model the small intestine and to study the role of NP ingestion on intestinal function (Guo et al, 2017, 2018; Mahler et al, 2012; Richter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is considered to be one of the primary causes of cytotoxicity, genotoxicity, inflammation, cell death and altered nutrient absorption induced by NP exposure in the gut [ 41 , 42 , 43 ]. We have also previously shown that AgNP ingestion causes excessive intracellular ROS induction in the Drosophila testis, leading to oxidative stress responsible for defects in germline stem cell homeostasis and a significant decrease in male fecundity [ 44 ].…”
Section: Resultsmentioning
confidence: 99%